Semi-automated hacksaw machine / Muhammad Fadhli Mohd Fuad ... [et al.] - Mohd Fuad, Muhammad Fadhli; Abdul Aziz, Abdul Halief Ziqri; Zulkarnain, Khairunnizam; Sarti, Muhammad Kassim Abdul Rasid
The advantage of using the semi-automatic hacksaw here already being stated that it helps in saving life with a lot of safety and protection factors installed inside the hacksaw. The price is surprisingly lower than other automated hacksaw which can target those people who love to bring their children to expose them with this kind of work and wants to have cheaper yet efficient hacksaw. This semi-automatic hacksaw also can best describe as suitable for any ages starting from 12 to the old people because the height and the degree in handling the handle can be adjusted well enough. It also helps people in practicing while doing work because it requires expertise and experience to use more advanced hacksaw. The faster the cutting motion of the hacksaw, the harder the hacksaw to be handled. The height of the table is high enough to avoid toddlers to reach the hacksaw while providing the suitable height for children to use it. Meaning that, with the function specified applies into the semi-automatic hacksaw, the safety of children playing around the hacksaw can be improved as the height of the table protects them from reaching into the blade cutter. Other than that, this semi-automatic hacksaw has a slider attached to the hacksaw blade which guides the hacksaw blade along it way. This process will improve the movement of the hacksaw during cutting process while avoiding the hacksaw to go sideways. The slider is made of material that withstand extreme activities and make the life span of the slider longer. Therefore, it is a very good product to sell in the market because it targets those who wants a long-life product with a cheaper price.